2015
DOI: 10.1007/s13361-015-1174-2
|View full text |Cite
|
Sign up to set email alerts
|

Base-Pairing Energies of Proton-Bound Dimers and Proton Affinities of 1-Methyl-5-Halocytosines: Implications for the Effects of Halogenation on the Stability of the DNAi-Motif

Abstract: Abstract. (CCG) n •(CGG) n trinucleotide repeats have been found to be associated with fragile X syndrome, the most widespread inherited cause of mental retardation in humans. The (CCG) n •(CGG) n repeats adopt i-motif conformations that are preferentially stabilized by base-pairing interactions of noncanonical proton-bound dimers of cytosine (C + •C). Halogenated cytosine residues are one form of DNA damage that may be important in altering the structure and stability of DNA or DNA-protein interactions and, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 72 publications
(105 reference statements)
7
21
0
Order By: Relevance
“…Two sequential dissociation pathways, both of which involve glycosidic bond cleavage occur in competition. In all cases, the excess proton is preferentially retained by the departing base, reaction , whereas retention of the excess proton by the sugar moiety is much less favorable (by more than an order of magnitude), reaction . The fragmentation patterns observed for the ( x Cyd)­H + ( x Cyd) base pairs parallel those observed in previous studies of protonated base pairs of cytosine nucleobase and cytidine nucleoside analogues as well as that of iosloated protonated cytidine nucleoside analogues using TCID , and IRMPD techniques.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Two sequential dissociation pathways, both of which involve glycosidic bond cleavage occur in competition. In all cases, the excess proton is preferentially retained by the departing base, reaction , whereas retention of the excess proton by the sugar moiety is much less favorable (by more than an order of magnitude), reaction . The fragmentation patterns observed for the ( x Cyd)­H + ( x Cyd) base pairs parallel those observed in previous studies of protonated base pairs of cytosine nucleobase and cytidine nucleoside analogues as well as that of iosloated protonated cytidine nucleoside analogues using TCID , and IRMPD techniques.…”
Section: Resultssupporting
confidence: 74%
“…The much stronger base-pairing interactions in the (Cyt)­H + (Cyt) base pair were thus interpreted as important contributors to the stability of genomic i -motif conformations. This initial study as well as a series of parallel follow-on investigations introduced increasing complexity to the (Cyt)H + (Cyt) base pair model for the i -motif by examining the effects of a series of modifications at the 1- and 5-positions of the nucleobase. Consistent with previous findings that 5-methylation stabilizes noncanonical i -motif conformations, the BPE of the (m 5 Cyt)­H + (m 5 Cyt) base pair was measured as 177.4 ± 5.3 kJ/mol, an increase of 7.5 ± 7.0 kJ/mol in the strength of base pairing. A somewhat smaller increase in the BPE to 173.4 kJ/mol was predicted by theory.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…TCID studies of the protonated base pairs of cytosine and its variants have been reported, with values listed in Table . It can be seen that the effects are subtle, with all base pairing energies (BPEs) within a range of 20 kJ/mol.…”
Section: Systemsmentioning
confidence: 99%
“…In the i -motif, based on the association of cytosine molecules protonated under neutral or slightly acidic conditions to form neutral cytosine—hemi-protonated cytosine base pairs (C:CH + ), two parallel-stranded duplexes are held together in an antiparallel orientation by intercalated C:CH + pairs [ 22 , 23 , 24 , 25 ]. Noteworthy, by decreasing the proton affinity of the N3 atom, 5-halogenation of 1-methylcytosine does not destroy the i -motif in DNA, but may alter the number of trinucleotide repeats required to induce the structural conversion from Watson and Crick ( WC ) base-pairing to the i -motif association [ 26 ].…”
Section: Introductionmentioning
confidence: 99%